Collaborations of biocultural hope: community science against Industrialisation in Northwest Australia - Wergin, Carsten (Ethnos, 2018)
The article discusses two community science projects organised in opposition to large-scale industrialisation in the Kimberley region of Northwestern Australia. Between 2006 and 2013, a significant conflict took place on the region’s Indian Ocean coast. It was triggered by the proposal of Australia’s largest independent oil and gas company Woodside Ltd. to build a $45 billion AUD liquefied natural gas facility at James Price Point, 50 km north of the tourist town of Broome. The community science initiatives highlight particular ways in which the local community was able not only to enter into the debate, but to significantly influence its outcome. This points towards alternate configurations of the political subjectivities involved in this conflict. Drawing on the Aboriginal notion of ‘living country’, the article presents these projects as signs of biocultural hope, that hint towards a world different from the one built on neoliberal ideals and dreams of economic opportunity alone.
Published online: 27 Apr 2016
Gesehen am 01.03.2017